Dense nanocrystalline yttrium iron garnet films formed at room temperature by aerosol deposition. (April 2016) - Johnson, Scooter D.; Glaser, Evan R.; Cheng, Shu-Fan; Hite, Jennifer
Abstract : Graphical abstract: Abstract : Highlights: We deposit yttrium iron garnet films at room temperature using aerosol deposition. Films are 96% of theoretical density for yttrium iron garnet. We report magnetic and structural properties post-deposition and post-annealing. Low-temperature annealing decreases the FMR linewidth. We discuss features of the FMR spectra at each anneal temperature. Abstract: We have employed aerosol deposition to form polycrystalline yttrium iron garnet (YIG) films on sapphire at room temperature that are 90–96% dense. We characterize the structural and dynamic magnetic properties of the dense films using scanning electron microscopy, X-ray diffraction, and ferromagnetic resonance techniques. We find that the as-deposited films are pure single-phase YIG formed of compact polycrystallites ∼20 nm in size. The ferromagnetic resonance mode occurs at 2829 G with a linewidth of 308 G. We perform a series of successive anneals up to 1000 °C on a film to explore heat treatment on the ferromagnetic resonance linewidth. We find the narrowest linewidth of 98 G occurs after a 750 °C anneal.